An assessment of polymeric materials and surface treated steels as cavitation erosion resistant materials - Barletta, A (Centre for Materials Engineering, 2016)
The object of the research described in this thesis was to optimise the choice of materials used for vital components of hydraulic machinery. Frequently these components are damaged by a process known as cavitation erosion and the operation and efficiency of machines are seriously impaired. Nineteen different polymers which have potential for use in hydraulic components have been eroded by liquid cavitation, employing the stationary specimen system. An attempt has been made to correlate the extent of erosion with the mechanical and chemical properties of the polymers. Modes of erosion of different materials were studied by scanning electron microscopy and a strong correlation was found between these modes and the resistance to erosion. Heterogenous polymers (mixture of two homogenous components), together with the poly amides and polyethylenes, showed the highest erosion resistances. The effect of prior immersion (3 weeks at 70°C) in either a dilute or concentrated form of hydraulic fluid has been investigated for both polyacetal and ultra high molecular weight polyethylene samples in order to simulate service conditions. The polyacetal samples showed improved erosion resistance relative to the samples stored in air or water (3 weeks at 70°C). In contrast, the ultra high molecular weight polyethylene samples failed in a catastrophic manner by solvent stress cracking.